Chagas disease of the colon and rectum. Issue 12 (December 1969) - Todd, I. P.; Porter, N. H.; Morson, B. C.; Smith, Barbara; Friedmann, C. A.; Neal, R. A.
Abstract : Chagas disease is a rare condition in patients anywhere but in Central and Latin America. This case is therefore reported because the patient was born in Britain and spent only a short time in an area where Chagas disease is endemic. It is believed that this patient is the first case of Chagas disease to be treated in Britain. Chagas disease causes a generalized degeneration of autonomic ganglia and usually presents as megaoesophagus or megacolon. The disease may also cause the heart to enlarge followed by cardiac failure.